ANALISIS FAKTOR FUNDAMENTAL DAN IMBAL HASIL SAHAM PERUSAHAAN ASURANSI DI BURSA EFEK INDONESIA - Muhammad Agusalim (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
Performance of insurance companies listed on the Indonesia Stock Exchange are Shown in the financial statement of the company, will show the fundamentals of the company that will asisst investors in making an investment decision. The purpose of this study was to determine and analyze: (1). Conditions of fundamental factors and stock return of insurance companies in the Indonesia Stock Exchange, (2). The fundamental factor that could determine the movement of the stock returns of insurance companies in the Indonesiaq Stock Exchange. This study was conducted over 6 monts, conducted in the Indonesia Stock Exchange. The study population by 10 Insurance companies listed on the Indonesia Stock Exchange . samples are 9 companies. This research is a quantitative research. Source of data is secondary data. The method of analysis is descriptive analysis and regression analysis and regression analysis to test classic assumptions. The result showed that : Coefficient of earning pershare (EPS) of 0.335 with sig. 0.020<0.05. the first hypothesis of the part one (H1.a) whichreads earnings pershare be a deciding factor in the movement of the stock returns of insurance companies in Indonesia Stock Exchange Accepted. Current ratio coefficient of 0.075 wiyh sig. 0.026<0.05 The first hipothesisof the part two (H1.b)which reads the current ratio can be a deciding factor in the movement of the stock returns of insurance companies in Indonesia Stock Exchange accepted. The coefficient of the return on assets amounted to 0.093 with sig. 0.019<0.05. the first hypothesis of the part three (H1.c) which reads return on assets may be the deciding factor in the coefficient of the return of insurance companies in Indonesia Stock Exchange accepted. Coefficient book value of 0.135 with sig. 0.353>0.05. The first hypothesis of the part four (H1.d)which reads the book value can be a deciding factor in the movement of the stock return of insurance companies in Indonesia Stock Exchange rejected. Price earning ratio coefficient of 0.003 with sig. 0.362>0.05 The first hypothesis of the part five (H1.e) which reads price earning ratio can be adeciding factor in the movement of the stock return of insurance companies in Indonesia Stock Exchange rejected. Debt to Equity Ratio of 0.224 with sign. 0.010<0.05. The first hypothesis of the part six (H1.f) which reads the Debt to Equity Ratio can be a deciding factor in the movement of the stock returns of insurance companies in Indonesia Stock Exchange accepted. Size coefficient of 0.285 with sign. 0.186>0.05. The first hypothesis of the part seven (H1.g) which reads the size can be a deciding factor in the movement of the stock returns of insurance companies in Indonesia Stock Exchange rejected. The conclucions of this study are : The average debt-equity ratio of insurance companies in the Indonesia Stock Exchange is greatest in 2013 and the smallest was in 2009. The average size of insurance companies in the Indonesia Stock Exchange is greatest in 2014 and most little was in 2009. The average return of the stock of insurance companies in Indonesia Stock Exchange is greatest in 2009 and the smallest was in 2011. Earnings pershare , the current ratio , return on asset and debt equity ratio can be the deciding factor the movement of the stock return. Can be deciding factor stock return movement. Book value, price-earnings ratio and size can not be adecisive factor stock return movement of insurance companies in the Indonesia Stock Exchange.